THE EFFECT OF MARKETING MIX ON INTEREST IN BUYING SOMETHINC SKINCARE PRODUCTS AT SHOPEE E-COMMERCE: Case Study on Students of Management Study Program, Faculty of Economics, Makassar State University - Azzahra, Asilah; Sahabuddin, Romansyah; Haeruddin, Muh. Ilham Wardhana; Hasbiah, Siti; Aswar, Nurul Fadilah (Journal Management & Economics Review (JUMPER), 2024)
This research aims to find out whether product, price, distribution, and promotion influence interest in buying Somehinc skincare products on Shopee E-Commerce. This research is a type of quantitative research. This research was carried out at Makassar State University with a sample size of 100 people. The analytical method used in this research is hypothesis testing with multiple linear regression. Based on the results of the validity and reliability tests, it shows that the statement items in the questionnaire are declared valid and reliable. The results of the t-test show that products and promotions have an insignificant effect, while price has a negative effect and distribution has an effect on interest in buying Somehinc skincare products on Shopee E-Commerce. And distribution has a positive and insignificant influence on interest in buying Somethinc skincare products on E-Commerce Shopee